Ethnic and Gender Differences in Strategies Used by Adolescents When Attempting to Quit or Reduce Smoking. Issue 3 (3rd May 2016) - Yurasek, Ali M.; Robinson, Leslie A.; Parra, Gilbert
ABSTRACT: Few adolescent smoking cessation programs have been able to match the success rate found in adult programs. The current study identified smoking cessation strategies used by adolescents and whether strategies differed as a function of ethnic, gender, or individual smoking level. Participants were 136 high school students who made an attempt to quit or reduce their smoking. Logistic regressions revealed that individuals making an actual quit attempt and African-American adolescents used cessation strategies presumed to be more effective. Adolescents are more likely to use informal cessation methods and may need to be provided with more information on effective quit strategies.